ҐЕНЕЗА СТАНОВЛЕННЯ ТА РОЗВИТКУ ПРАВ ТА СВОБОД ЗАСУДЖЕНИХ В УКРАЇНІ - Ковальов, Артем Вадимович (SUPREMANCE OF LAW, 2017)
The article analyzes the historical aspects of the formation and development of the rights and freedoms of prisoners in our state since the days of Kievan Rus to the present day. Investigated normative documents that define the rights and freedoms of prisoners. It is stated that the rights and freedoms of prisoners in need of improvement. Disclosure of the effects of historical and legal phenomena in the process of execution and serving sentences in Ukraine, covered their role in the reform of the penitentiary system.